THE USE OF CHILDREN'S STORIES IN LEARNING ENGLISH VOCABULARY : PENGGUNAAN CERITA ANAK-ANAK DALAM PEMBELAJARAN KOSAKATA BAHASA INGGRIS - Felin Dyah Nur Arifah; Khaulah Afifa; Teni Okty Handayani; Farur Rozi; Ellianawati (STKIP Subang, 2025)
English is a foreign language that is quite difficult to understand. However, children's storybooks provide a solution for learning English. The use of storybooks in teaching English vocabulary can improve children's English language skills. This study aims to determine (1) the use of children's fairy tales in English vocabulary learning, (2) the process of implementing learning using fairy tales, (3) students' responses to fairy tale-based learning, (4) supporting and inhibiting factors in the use of children's fairy tales. This study used a qualitative method with observation and interview techniques. This study was conducted at SDN Padarek III on fourth-grade students. The results of the study show that the use of children's fairy tales in learning can improve students English vocabulary skills, and students responses to learning using fairy tales are very positive, where children who tend to be passive become active when learning, learning becomes fun, and students are motivated to learn english. The use of English fairy tales as a teaching medium for fourth grade students can foster students' literacy skills and mastery of new vocabulary.